THE RESEARCH WORK AS A WAY OF RECEIVING PROFESSIONAL SKILLS FOR IT STUDENT (Journal of Information Technologies in Education (ITE), 2012)
The article is devoted to the work of students majoring in computer science IT structure of university students as a way of professional competencies. The problems of improving the quality of training and adapting in real professional environment. The article highlights the issue of project work, with which there is increased motivation to obtain IT skills specialist. Revealed the basic principles, methods of organization of scientific – research work of students and stages of research competencies.
Keywords: innovation; professional IT expertise; professional practice; project work; scientific – research structures; the successful employment